Penerapan Inkubator Penetas Telur Ayam Secara Otomatis Berbasis Internet Of Things (Iot) Dalam Upaya Peningkatan Usaha Peternakan Ayam Di Desa Oelbubuk, Kecamatan Molo Tengah, Kabupaten Timor Tengah Selatan - Bale, Jefri; Tarigan, Ben; Selan, Rima; Modok, Renold (Journal Of Human And Education (JAHE), 2023)
The Community Service Program through community partnerships is implemented to support national programs in improving the community's economy and efforts to prevent stunting and by increasing chicken farming businesses through the use of egg hatching incubator. Mitra is a community consisting of 20 (twenty) people and is part of the "Safe Smala" livestock farming group in Oelbubuk Village, Central Molo District, South Central Timor Regency, East Nusa Tenggara Province. PkM activities will last for 6 (six) months with the involvement of 3 (three) lecturers and 3 (three) students. Through this activity, it is hoped that the community will have the skills to be able to use chicken egg-hatching incubators and the efficiency of successful egg-hatching will increase. The methods that will be implemented in this PKM include the preparation stages, implementation of activities, monitoring and evaluation, and preparation of reports. Preparations that will be made include observation, location surveys, and conveying the problems and solutions that will be taken in implementing the activity. Implementation takes the form of designing tools, testing tools, increasing the capacity of partners through training and use of tools, assistance in maintaining tools, monitoring stages by the implementing team and evaluating program implementation. The expected outputs from this PKM activity include achieving program target outputs, and output achievement targets in the form of publication of activity results in national journals and at scientific meetings. Keywords: Oelbubuk, stunting, incubator, chicken eggs.